Development and validation of a cardiovascular disease risk-prediction model using population health surveys and dietary indices: the Cardiovascular Disease Population Risk Tool – Nutrition (CVDPoRT-Nutrition). (2022) - Jessri, Mahsa; Eddeen, Anan Bader; Hennessy, Deirdre; Bernstein, Jodi; Sanmartin, Claudia; Bennett, Carol; Manuel, Douglas
No abstract available